Microfluidic array chip for highly parallel genomic and transcriptomic applications - Naveen Ramalingam (2012)
The Polymerase Chain Reaction (PCR) is an enzyme-based technique to amplify a single or few copies of Deoxyribose Nucleic Acid (DNA) in an exponential process, generating millions of copies of a known DNA sequence. The technique relies on thermal cycling; consisting of repeated cycles of heating and cooling of a reaction for DNA melting, target identification and enzymatic replication of the target DNA. The PCR technique is widely used for diagnosis, prognosis of diseases and enumeration of pathogen loads. Conventional PCR instruments are bulky, limiting its use in the field, but rapid development of miniaturized total analysis systems (μTAS) enables commercialization of point-of-care devices. In resource-limited settings, it is impractical to get access to a diagnostic laboratory having sophisticated instruments and in such settings, it is desirable to use disposable point-of-care high-throughput diagnostic chips that do not require liquid handling or pumping instruments for sample distribution among an array of reactors. In addition to the pump-less sample loading method, the challenge to seal an array of reactors without the use of microvalves or mechanical parts persists. Implementation of microvalve array adds complexity to the chip fabrication and operation processes, and reduces the space on the microchip. The current point-of-care, PCR-based biochips are limited by its capability to test multiple samples or different gene targets. In this doctoral work, a high-throughput, primer pair pre-loaded quantitative PCR chip platform for parallel analyses of multiple gene targets is developed. The PCR mixture distribution among an array of microreactors and subsequent isolation of the reactors were solely realized by a two-step surface tension-based microfluidic scheme, which eliminates the use of pumps, valves and liquid handling instruments. Sample loading and reactor sealing is achieved by implementing an unbalanced Young’s force achieved by fabricating poly(dimethylsiloxane) (PDMS) and glass surface’s with different wettability. The reactor-to-reactor diffusion of the pre-loaded primer pairs is investigated to eliminate the possibility of primer cross-contamination. Key technical issues such as primer pair degradation due to chip bonding conditions and bubble generation due to different PDMS-glass bonding methods are investigated. The capability of the developed PCR array chip is demonstrated by simultaneous (parallel) amplification of twelve different gene targets against cDNA template for risk prediction of human hepatocellular carcinoma and simultaneous detection of multiple water-borne pathogens. In addition, a microfluidic device harboring an array of open/unsealed reactors was developed for isothermal amplification and detection of SARS cDNA template. Another version of high-throughput PCR array chip was developed as PDMS matrix chip. Sample loading and microwell sealing in this chip was achieved by vacuum and positive-pressure based loading of liquid PDMS prepolymer. Finally, the PDMS matrix chip was applied to solve an important clinical application. A microfluidic digital PCR was developed on the PDMS matrix chip for absolute quantification of live Methicillin-Resistant Staphylococcus aureus (MRSA) in mixed bacterial samples.